2017
DOI: 10.5194/hess-21-6007-2017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an ensemble seasonal streamflow forecasting system for Australia

Abstract: Abstract. Despite an increasing availability of skilful longrange streamflow forecasts, many water agencies still rely on simple resampled historical inflow sequences (stochastic scenarios) to plan operations over the coming year. We assess a recently developed forecasting system called "forecast guided stochastic scenarios" (FoGSS) as a skilful alternative to standard stochastic scenarios for the Australian continent. FoGSS uses climate forecasts from a coupled oceanland-atmosphere prediction system, post-pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…However, employing EIOR requires information about the streamflow forecast to alleviate the risk of flooding.The recent advancements of the meteorological and hydrological forecast systems provide an unprecedented opportunity for employing flexible operation rules rather than fixed ones for reservoir systems [19][20][21]. Combining seasonal meteorological forecasts with hydrological models at continental-scale has provided several continental-scale seasonal hydro-meteorological forecasting systems [22][23][24], such as the European Flood Awareness System [25], the Australian Government Bureau of Meteorology Seasonal Streamflow Forecasts [26], and the National Hydrologic Ensemble Forecast Service, USA [27]. Several studies have demonstrated that a skillful streamflow forecast can enhance the efficiency of water allocation systems to manage the trade-off between hydropower, irrigation, municipal, and environmental services [28][29][30][31].…”
mentioning
confidence: 99%
“…However, employing EIOR requires information about the streamflow forecast to alleviate the risk of flooding.The recent advancements of the meteorological and hydrological forecast systems provide an unprecedented opportunity for employing flexible operation rules rather than fixed ones for reservoir systems [19][20][21]. Combining seasonal meteorological forecasts with hydrological models at continental-scale has provided several continental-scale seasonal hydro-meteorological forecasting systems [22][23][24], such as the European Flood Awareness System [25], the Australian Government Bureau of Meteorology Seasonal Streamflow Forecasts [26], and the National Hydrologic Ensemble Forecast Service, USA [27]. Several studies have demonstrated that a skillful streamflow forecast can enhance the efficiency of water allocation systems to manage the trade-off between hydropower, irrigation, municipal, and environmental services [28][29][30][31].…”
mentioning
confidence: 99%
“…The forecasted datasets for determining the expected reservoir inflow were obtained from an experimental streamflow forecasting system called Forecast Guided Stochastic Scenarios (FoGSS), available for the time period 1982-2009 (Bennett et al, 2017). Two different datasets from FoGSS were used.…”
Section: Data and Informationmentioning
confidence: 99%
“…The streamflow forecasting system "Forecast Guided Stochastic Scenarios" (FoGSS) is an experimental forecasting system, which has been developed and tested for the Australian continent (Bennett et al, 2016(Bennett et al, , 2017Turner et al, 2017). FoGSS is an ensemble streamflow forecast in the form of monthly time series for a 12-month forecast horizon.…”
Section: Forecast Guided Stochastic Scenarios (Fogss)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case when using the Ensemble Streamflow Prediction (ESP) method, a widely applied technique to generate ensembles of possible future scenarios of streamflow over several weeks and months ahead. The method is based on using a continuous hydrological model to estimate initial hydrological conditions (using real-time meteorological data as input) and future meteorological forecasts (based on historical sequences of meteorological data) to obtain streamflow predictions several months ahead (see recent applications in, for instance, Crochemore et al, 2016;Bennett et al, 2017;Arnal et al, 2018;Harrigan et al, 2018). Reliable and consistent long-term historic meteorological data are therefore also crucial when running seasonal forecasting systems.…”
Section: Introductionmentioning
confidence: 99%